2019
DOI: 10.1093/neuonc/noz126.216
|View full text |Cite
|
Sign up to set email alerts
|

P12.05 Evaluating the compatibility of tumor treating electric fields with key antitumoral immune functions

Abstract: BACKGROUND TTFields has the ability to induce immunogenic cell death (ICD). As immunotherapy and TTFields have different mechanisms of action (MOA), combining these therapies is a rational approach. Contrarily, TTFields may interfere with immune functions critical for effective T cell function. MATERIAL AND METHODS We cultured T cells from healthy donors’ peripheral blood or from viably dissociated glioblastoma samples under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Diamant et al reported no impact on T-cell counts secondary to TTFields (20). In vitro studies of T-cell functionality such as induced cytotoxic degranulation and direct cytotoxic activity were not inhibited by TTFields (20). Taken together, the preclinical data, to date, suggests that TTFields do not induce local and systemic immunosuppressive effects and supports a favorable clinical safety profile for TTFields.…”
Section: Discussion Ttfields Impact On the Immune Systemmentioning
confidence: 90%
See 1 more Smart Citation
“…Diamant et al reported no impact on T-cell counts secondary to TTFields (20). In vitro studies of T-cell functionality such as induced cytotoxic degranulation and direct cytotoxic activity were not inhibited by TTFields (20). Taken together, the preclinical data, to date, suggests that TTFields do not induce local and systemic immunosuppressive effects and supports a favorable clinical safety profile for TTFields.…”
Section: Discussion Ttfields Impact On the Immune Systemmentioning
confidence: 90%
“…Hematopoiesis has been demonstrated to be unaffected by TTFields as hematopoietic stems cells, residing in the bone marrow, are shielded due to the high bone impedance resulting in significantly lower field intensities (19). Diamant et al reported no impact on T-cell counts secondary to TTFields (20). In vitro studies of T-cell functionality such as induced cytotoxic degranulation and direct cytotoxic activity were not inhibited by TTFields (20).…”
Section: Discussion Ttfields Impact On the Immune Systemmentioning
confidence: 99%